EFFECTIVENESS ANALYSIS OF THE LAND AND BUILDING TAX OF RURAL AND URBAN AREAS (PBB-P2) CONTRIBUTION TO LOCAL OWN-SOURCE REVENUE (PAD) OF TUBAN REGENCY - Wicaksono, Galih; Kusumaningrum, Nurcahyaning Dwi; Safitri, Putri Apriliani Rahmah (International Journal of Multidisciplinary Research and Literature, 2022)
The Land and Building Tax of Rural and Urban Areas (PBB-P2) are one of the most important local taxes, which has the potential to increase Local Own-Source Revenue (PAD). In the current era of regional autonomy, the government is in direct need of large enough funds to meet government financing in carrying out regional development through Local Own-Source Revenue (PAD), which is a source of regional revenue. This study aims to determine: (1) to determine the effectiveness of the Rural and Urban Land and Building Tax revenue (PBB-P2), (2) to determine the contribution of The Land and Building Tax of Rural and Urban Areas (PBB- P2) to Regional Original Income. (PAD). This research method uses descriptive quantitative methods and uses secondary data types. Based on the results of the study, it shows that for effectiveness, it is in the very effective category, because the revenue is greater than the target. And then, the contribution level of The Land and Building Tax of Rural and Urban Areas (PBB-P2) in Tuban Regency in 2018-2020 is still less effective. The Contribution rate each year always in the very poor category, but the revenue target and realization of The Land and Building Tax of Rural and Urban Areas (PBB-P2) on Regional Original Income have increased every year, the same is the case with the realization of Local Own-Source Revenue (PAD) every year has increased